SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN ASISTEN LABORATORIUM BERBASIS WEB MENGGUNAKAN LOGIKA FUZZY (Studi Kasus : Laboratorium Witana, Universitas Pamulang) - Muhammad Bahrein (CV. Multi Kreasi Media, 2024)
The Witana Laboratory is one of the Laboratories of the Faculty of Engineering, University of Pamulang. The Witana Laboratory involves laboratory assistants in carrying out all of its activities. Laboratory assistants must have knowledge, expertise and skills in the field of heavy equipment. To be able to recruit the right laboratory assistant, it is necessary to hold a selection process. There are several assessment criteria such as CV scores, written test scores, assistant interviews and analyst interviews. The problem with the selection process is that making decisions in this way allows for errors in the assessment process and results in an inaccurate assessment. Common problems that often occur in the assessment process are usually subjective, especially if there are several laboratory assistant candidates who have the same total score as other laboratory assistant candidates, making the selection process difficult for laboratory assistant candidates. In addition, the registration process on the current system is still carried out by submitting files directly to the laboratory assistant so that registration takes longer and the process becomes inefficient. Therefore, a computerized decision support system is needed in accepting new laboratory assistants. This application is designed using fuzzy logic. With this application, decision making for laboratory assistant admissions can provide more precise, effective and efficient results.